Improvement of Production Line in the Automotive Industry Through Lean Philosophy - Azevedo, J. (2020)
This work refers to concepts and definitions of Lean Philosophy. The main targets were to study how waste reduction can be achieved on a production scenario, by identifying added-value operations, enhance productivity, levelling and over-processing reduction. The project behind this study is a massive one, which involves the installation of seven final production lines and more seven pre-assembly lines, being considered by the company, a project that must be as profitable as possible. After implementation and validation, costs were evaluated and the savings reached 10,9 % (2 159 000 €) considering all costs of industrialization.